2007
DOI: 10.1097/ftd.0b013e31805c73f1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Liquid Chromatography-Mass Spectrometric Assay for Tacrolimus in Liver Biopsies After Hepatic Transplantation: Correlation With Histopathologic Staging of Rejection

Abstract: The aims of this work were both to validate a sensitive and specific method to quantify tacrolimus (TAC) in liver biopsies after hepatic transplantation and to evaluate the predictive value of either tissue or blood TAC concentrations for rejection in 146 adult patients under a TAC-based immunosuppression. Trough blood levels were monitored daily during the hospital stay by immunoassay. Liver biopsies were routinely performed at day 7 posttransplantation. The tissue assay was developed by liquid chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 49 publications
4
60
0
Order By: Relevance
“…Measured amounts of TAC from each sample were standardized and converted in concentrations using their sample-specific MCV [28][29][30], obtained for each sample through the automated cell counter. This represents a strong novelty point respect to the previous methods [15][16][17][18]31], because the standardization of analytical results on the basis of the real cell volume in the single sample removes an important source of bias. Moreover, this allowed a correct comparison and correlation between intra-PBMC and whole-blood concentrations of TAC.…”
Section: Discussionmentioning
confidence: 96%
“…Measured amounts of TAC from each sample were standardized and converted in concentrations using their sample-specific MCV [28][29][30], obtained for each sample through the automated cell counter. This represents a strong novelty point respect to the previous methods [15][16][17][18]31], because the standardization of analytical results on the basis of the real cell volume in the single sample removes an important source of bias. Moreover, this allowed a correct comparison and correlation between intra-PBMC and whole-blood concentrations of TAC.…”
Section: Discussionmentioning
confidence: 96%
“…These studies, however, exclusively investigated the influence of genetic polymorphisms on Tac blood concentration and/or dose requirement. It has been recently reported that hepatic concentrations appear to be a better marker of histological rejection than trough blood concentrations [4]. In this study, Capron et al showed that Tac hepatic concentrations varied markedly among patients and were well correlated with the histological rejection score (Banff score), whereas no relation was found between the Banff score and trough blood concentrations.…”
mentioning
confidence: 86%
“…The protocol of the present pharmacogenetic study was appended retrospectively to the previously described protocol of Capron et al [4]. Liver donors (n = 150) were all cadavers and all recipients had Tac-based immunosuppressive therapy.…”
Section: Population Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Liver biopsy during drugand toxin-induced liver injury is of course not commonly used for this purpose. However, development of liquid chromatography-mass spectrometric (LC-MS/MS) assays for tissue specimens of tacrolimus from liver biopsy have been shown to be better correlated to histopathologic rejection scores than conventional immunoassays of ordinary blood concentrations (Capron et al, 2007). With further development of highly sensitive LC-MS/MS assays, specific determination of substances with metabolites can hopefully be useful in the context of drug-and toxin-induced liver injury.…”
Section: Further Studies and Use Of Retrospective Datamentioning
confidence: 99%